Kickstarting trans*: The crowdfunding of gender/sexual reassignment surgeries. (February 2015) - Farnel, Megan
The crowdfunding of gender/sexual reassignment (G/SRS) surgeries is a recent and controversial phenomenon on which there currently exists no academic commentary. This article considers three particular G/SRS crowdfunding campaigns with a focus on two primary elements: the aesthetic and commodified positions of trans* bodies, and the role of the potential backers, the crowds of crowdfunding. Both, I argue, are shaped by specific platform regulations as well as by broader social and political norms specific to and beyond trans* bodies. At stake in these distinctions are the extent to which trans* bodies are permitted to be defined as art and/or commodities, as well as the conditions under which backers are compelled (or not) to provide emotional, financial and political support for trans*-positive causes. Digital media, I conclude, is increasingly playing a role in defining, producing and challenging the modes of normativity that determine the livability of life for precarious subjects.